Brazilian Loneliness Scale: Evidence of Validity Based on Relations to Depression, Anxiety and Stress - Barroso,Sabrina Martins (2021)
Abstract This paper aimed mainly to investigate the relationships between Brazilian Loneliness Scale (UCLA-BR) and the levels of depression, anxiety and stress in Brazilian college students. These concepts were assessed using validated scales (Patient Health Questionnaire - PHQ-9, Depression, Anxiety and Stress Scale - DASS-21, Beck Anxiety Inventory - BAI and Lipp Stress Symptom Inventory - ISSL). A total of 325 college students participated and responded all the instruments. Descriptive, correlational and group differences analyzes were conducted. The prevalence of depression, anxiety and stress varied depending on the instrument used. UCLA-BR presented evidence of validity based on relationships with depression, anxiety and stress, especially depression (assessed by DASS-21). Analysis of measurement scales can help to understand aspects of college students’ mental health.